TAWZIF AL-WASA'IL AL-TAKLIMIYAH AL-HADITHAH LI-TAKLIM AL-BALAGHAH AL-'ARABIYAH: AL-'ARUD AT-TAQDIMIYAH (POWERPOINT) NAMUDHAJAN - Samae, Abdulghaffar; Taher, Rusdee (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
This paper aims to provide practical suggestions for teaching Arabic rhetoric to non-Arabic speaking university students. These suggestions are presented in PowerPoint slides and their use is explained in a way that is consistent with the content of the material. These suggestions were tested on two groups of students enrolled in Bachelor's programs in Sharia, Islamic Studies, and Foundations of Religion at Sultan Azlan Shah University in Malaysia. The problem with teaching non-Arabic speakers a new science in Arabic language is that their level in the language is uneven and most of them are below the required level to study a subject that requires a strong foundation in the language, especially when dealing with poetry and eloquent sayings that are the subject of rhetoric. This poses a challenge for both the teacher and the student. The study relied on a descriptive approach to create and present slides, and to explain the principles and considerations that should be taken into account. The study arrived at a number of results, the most important of which is the necessity of using these modern methods, which are no longer a luxury or a standard for evaluating the teacher alone, as the study recorded an improvement in students' understanding of rhetoric lessons after using these methods compared to not using them.